Analisis Survival Strategy Nelayan Tradisional di Pulau Miangas Kabupaten Kepulauan Talaud Provinsi Sulawesi Utara - Wilson M. A. Therik; Frinsiska Jelinda Sahadula (Yayasan Bina Darma, 2017)
People in Miangas rely on fisheries and agriculture products as their main source of livelihood. They encounter with several problems such as: storm and big waves, limited technology and transportation, illegal fishing by the Filipino fishermen, the lack of quality of the local fishermen, inadequate service and health facilities, and poor quality of education. Starting from these problems and difficulties, the purpose of this research is to find out the survival strategy by local fishermen on Miangas Island, Talaud regency, North Sulawesi. This research used descriptive-qualitative approach which based on interviews, observation, documentation study, and data analysis inductive model. The results of this study are: (1) Buildings a relationship with a Filipino fisherman; local fisherman weaves relationship with Filipino fisherman and utilize their expertise to find fish. (2) The role of the fishermans wife in managing household expenses (financial management), become one of survival strategies that are no less importent thant other strategies. (3) Fishermans in Miangas give informal and formal education for their children so that later they can survive. (4) The fisherman in Miangas island use the natural resources to get another icome when the weather is bad. Besidesthe abundanceof natural resourceson the island ofMiangasprovides allbasicfoodrequired bytraditionalfishermenon the island ofMiangas, so they cansurvive.